Shifting Listening Niches: Effects of the COVID-19 Pandemic - Hurwitz, Emily Rose; Krumhansl, Carol Lynne (Frontiers in Psychology, 2021)
The term ‘listening niche’ refers to the contexts in which people listen to music, including what music they are listening to, with whom, when, where, and with what media. The first experiment investigates undergraduate students’ music listening niches in the initial COVID-19 lockdown period, four weeks immediately after the campus shut down abruptly. The second experiment explores how returning to a hybrid semester, the “new normal”, further affected these listening habits. In both experiments, the participants provided a list of their most frequently listened-to songs during the respective period of time. From these, they identified one song that seemed most associated with this period, their “signature song”, and stated why this song seemed relevant. These reasons were coded on nine underlying themes. Three clusters were found to underlie the themes: (1) emotional responses; (2) memory associations; (3) discovery of new music. We identified songs and reasons for selecting them that represented the three clusters and related these to the lyrical content. Compared to before the pandemic, participants in both experiments report listening more in general and on Spotify, but there were no differences in listening between lockdown and the new normal. Who they were listening with shifted overtime from family members, to significant others and finally to other friends and roommates. These results demonstrate how students listen to and find new music that is meaningful to them during this unprecedented pandemic.